2001
DOI: 10.1053/jhep.2001.29374
|View full text |Cite
|
Sign up to set email alerts
|

Disturbances in hepatic cell-cycle regulation in mice with assembly-deficient keratins 8/18

Abstract: Simple epithelial tissues such as liver and pancreas express keratins 8 (K8) and 18 (K18) as their major intermediate filament proteins. K8 and K18 null mice and transgenic mice that express mutant K18 (K18C) manifest several hepatocyte abnormalities and demonstrate that K8/18 are important in maintaining liver tissue and cell integrity, although other potential functions remain uncharacterized. Here, we report an additional abnormal liver phenotype, which is similar in K8 null, K18 null, and K18C mouse models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 47 publications
4
45
0
2
Order By: Relevance
“…Untreated K8-null and K18-null mice have normal-appearing exocrine pancreata apart from rare areas with abnormal structures that we have described earlier 23 Table 3B). After 14 days, the survivor K8-null and all the other mice had lost their acini and the tissue was replaced by ducts, fat and inflammation (Figure 2e-h and Table 3B).…”
Section: Dramatic Resistance and Recovery From Cvb4-p Virus Infectionsupporting
confidence: 66%
“…Untreated K8-null and K18-null mice have normal-appearing exocrine pancreata apart from rare areas with abnormal structures that we have described earlier 23 Table 3B). After 14 days, the survivor K8-null and all the other mice had lost their acini and the tissue was replaced by ducts, fat and inflammation (Figure 2e-h and Table 3B).…”
Section: Dramatic Resistance and Recovery From Cvb4-p Virus Infectionsupporting
confidence: 66%
“…Notably, we found that both vimentin negative MCF-7 cells and vimentin positive HeLa and Panc-1 cells fail to target desmoplakin at cell borders. The role of keratins in the maintenance of desmosomes is also supported by findings of a careful histological characterisation of liver lesions in both K8 and K18 null mice (Toivola et al, 2001). Livers of keratin null mice showed large areas that were devoid of both desmoplakin and filamentous actin staining (Toivola et al, 2001).…”
Section: Periplakin Participates In Re-organisation Of Keratin Intermmentioning
confidence: 90%
“…The role of keratins in the maintenance of desmosomes is also supported by findings of a careful histological characterisation of liver lesions in both K8 and K18 null mice (Toivola et al, 2001). Livers of keratin null mice showed large areas that were devoid of both desmoplakin and filamentous actin staining (Toivola et al, 2001). One possible reason for mistargeting of desmoplakin in the absence of keratins could be altered function of plakophilins in the recruitment of desmoplakin.…”
Section: Periplakin Participates In Re-organisation Of Keratin Intermmentioning
confidence: 93%
“…45 In addition, absence of K8/K18 proteins as a consequence of K8 gene ablation in mice results in alterations in cell cycle regulation. 46 Also, cell lines expressing epidermal keratin mutants that cause epidermolysis bullosa simplex manifest an accentuated stress-activated protein kinase response compared with cells that express their WT counterparts. 47 Although the details of how keratin mutations influence gene transcription has yet to be investigated, apoptosis is generally a downstream consequence of oxidative injury.…”
Section: Discussionmentioning
confidence: 99%